Endothelial TLR4 Expression Mediates Vaso-Occlusive Crisis in Sickle Cell Disease - Beckman, Joan D.; Abdullah, Fuad; Chen, Chunsheng; Kirchner, Rachel; Rivera-Rodriguez, Dormarie; Kiser, Zachary M.; Nguyen, Aithanh; Zhang, Ping; Nguyen, Julia; Hebbel, Robert P.; Belcher, John D.; Vercellotti, Gregory M. (Frontiers in Immunology, 2021)
Heme, released from red blood cells in sickle cell disease (SCD), interacts with toll-like receptor 4 (TLR4) to activate NF-κB leading to the production of cytokines and adhesion molecules which promote inflammation, pain, and vaso-occlusion. In SCD, TLR4 inhibition has been shown to modulate heme-induced microvascular stasis and lung injury. We sought to delineate the role of endothelial verses hematopoietic TLR4 in SCD by developing a TLR4 null transgenic sickle mouse. We bred a global Tlr4-/- deficiency state into Townes-AA mice expressing normal human adult hemoglobin A and Townes-SS mice expressing sickle hemoglobin S. SS-Tlr4-/- had similar complete blood count and serum chemistries as SS-Tlr4+/+ mice. However, SS-Tlr4-/- mice developed significantly less microvascular stasis in dorsal skin fold chambers than SS-Tlr4+/+ mice in response to challenges with heme, LPS, and hypoxia/reoxygenation (H/R). To define a potential mechanism for decreased microvascular stasis in SS-Tlr4-/- mice, we measured pro-inflammatory NF-κB and adhesion molecules in livers post-heme challenge. Compared to heme-challenged SS-Tlr4+/+ livers, SS-Tlr4-/- livers had lower adhesion molecule and cytokine mRNAs, NF-κB phospho-p65, and adhesion molecule protein expression. Furthermore, lung P-selectin and von Willebrand factor immunostaining was reduced. Next, to establish if endothelial or hematopoietic cell TLR4 signaling is critical to vaso-occlusive physiology, we created chimeric mice by transplanting SS-Tlr4-/- or SS-Tlr4+/+ bone marrow into AA-Tlr4-/- or AA-Tlr4+/+ recipients. Hemin-stimulated microvascular stasis was significantly decreased when the recipient was AA-Tlr4-/-. These data demonstrate that endothelial, but not hematopoietic, TLR4 expression is necessary to initiate vaso-occlusive physiology in SS mice.